DAMPAK PDRB DAN PERTUMBUHAN JUMLAH PENDUDUK TERHADAP PENINGKATAN JUMLAH PENDUDUK MISKIN DI PROVINSI RIAU - Herman, Herman (Eko dan Bisnis: Riau Economic and Business Review, 2024)
Abstract: This research aims to see the impact of population and GDP growth on the increase in the number of poor people in Riau Province. The source of the data obtained is secondary data obtained from BPS Riau in the form of numbers with a time series from 2013 to 2022. The data analysis technique uses multiple linear regression, classical assumption testing, and hypothesis testing. The research results show that for the classical assumption test there are no problems with all independent variables (the data is suitable for use in this research). the results of multiple linear regression obtained KMK= 8,131-0,389GRDP+0,196PDK. and the results of the t test F test show that all independent variables have a significant effect on the dependent variable and the magnitude of the effect is 78.3 percent.